HIGH RESOLUTION OF COMPUTED TOMOGRAPHY FINDINGS IN SPUTUM AFB POSITIVE CASES (The Research of Medical Science Review, 2025)
OBJECTIVE: To evaluate the High-Resolution Computed Tomography (HRCT) findings in sputum Acid-Fast Bacillus (AFB) positive cases. METHODOLOGY: This cross-sectional study was conducted at the Department of Radiology, Sindh Govt Hospital Korangi No. 5 Karachi, during December 2023 to January 2024 on 80 participants, selected through non-probability consecutive sampling. All patients underwent sputum AFB smear and culture before HRCT and chest radiography. HRCT scans were performed using an MDCT scanner. Data analysis was conducted using SPSS 26, with p ≤ 0.05 considered statistically significant. RESULTS: This investigation encompassed a cohort of 80 participants with a mean age of 41.01 ± 14.47 years; 60% of the subjects were identified as male. The predominant high-resolution computed tomography (HRCT) findings encompassed centrilobular nodules (90.0%), lobular consolidation(82.5%), cavitation(73.8%), and a tree-in-bud appearance(63.7%). Observations of lesser frequency consisted of lymphadenopathy (8.8%) and miliary nodules(5.0%), thereby underscoring the critical role of HRCT in the identification of distinctive pulmonary tuberculosis manifestations. CONCLUSION: This study, with sputum AFB positivity, evaluated HRCT findings in patients with PTB, and these included centrilobular nodules, lobular consolidation, cavitation, and a tree-in-bud appearance. HRCT can delineate the extent of disease better than any other imaging modality, where microbiological tests may fail. HRCT is of great help in a quick diagnosis and treatment of PTB as it shows high sensitivity in identifying early and subtle parenchymal change. Further work is needed to explore its prognostic significance and ability to guide therapeutic approaches to mitigate these poor patient outcomes.